Comparison of two methods of measuring physical activity and its related components among middle age women: Pedometer versus self-report - Mohammadreza Ghaneapur; Mohamad Ezati Asar; Marzieh Belji Kangarlou; Elahe Saleh (PLoS ONE, 2025)
Introduction Physical activity is essential for health maintenance across various dimensions; however, sedentary behavior remains widespread in numerous societies. Notably, women often exhibit higher levels of sedentary behavior than men, potentially exacerbating complications related to motherhood. This study aims to assess and compare physical activity levels in middle-aged women (30–45) using self-reported measures and pedometers while exploring associated factors in the context of reproductive health. Methods This study analyzed secondary data from a randomized controlled trial involving 91 women aged 30–45 from Semnan University of Medical Sciences. Participants completed a validated 12-item questionnaire and wore Omron Style Pro-2 pedometers for one week to assess physical activity levels. Women were categorized as active or inactive based on self-reports and pedometer data. Statistical analyses were conducted using SPSS version 27. Participants provided informed consent, ensuring confidentiality throughout the study. Results The study involved 91 women with a mean age of 27.4 years, of whom 82.6% were married. Only 11.7% self-reported as “low active,” while pedometer data revealed that 94.5% were inactive or had insufficient physical activity. A significant relationship was found between the number of children and physical activity levels, with women who had children being more active (p =  0.035). No correlation was observed between self-reported activity and pedometer measurements, indicating women often overestimate their physical activity levels. Discussion This study highlights the inaccuracies in self-reported physical activity assessments. Most women were found to be physically inactive, with the number of children influencing their activity levels. These findings underscore the need for interventions to increase women’s physical activity. Conclusion These findings bear important implications for health policy within communities. Further research involving larger sample sizes across various age and gender demographics is warranted to enhance our understanding of physical activity patterns and inform targeted interventions.